2011
DOI: 10.1186/1475-2867-11-30
|View full text |Cite
|
Sign up to set email alerts
|

Potassium bicarbonate and D-ribose effects on A72 canine and HTB-126 human cancer cell line proliferation in vitro

Abstract: BackgroundThe synergic action of KHCO3 and D-ribose is tested on A72 and HTB-126 cell lines proliferation using K:D-Rib solution. Altered Na+/K+ ATPase expression and activity were shown in patients with cancer. Studies in human epithelial-derived malignancies indicate that K+ depletion also occurs, contributing to the increased intracellular Na+/K+ ratio [1]. D-ribose transformed to piruvate, enters into the Krebs's cycle and has a key role on energetic metabolism. The up-regulation of glycolysis in tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Previous studies have revealed that hybrid-type intramolecular G-quadruplexes appear to be the predominant conformation formed in human telomeric sequences in solution in the presence of K + (72,73). It has been reported that the increase of K + transported into the cells alters the shape of G-quadruplexes (30). Therefore, the time-dependent effect observed in the present study upon treatment with A and K may reflect the time required for G-quadruplexes in tumor cells to shift from the Na + to the K + form.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have revealed that hybrid-type intramolecular G-quadruplexes appear to be the predominant conformation formed in human telomeric sequences in solution in the presence of K + (72,73). It has been reported that the increase of K + transported into the cells alters the shape of G-quadruplexes (30). Therefore, the time-dependent effect observed in the present study upon treatment with A and K may reflect the time required for G-quadruplexes in tumor cells to shift from the Na + to the K + form.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism causes the release of calcium from its intracellular deposits and a simultaneous increase in glucose uptake, thus enhancing mitogenic stimulation (27,56,57). It has been previously demonstrated that the administration of K ascorbate produced anticancer effects in vitro (30,58), possibly due to the carrier properties of A, which allows a rapid diffusion of K into the cells, leading to the inhibition of tumor cell proliferation (27,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our most recent work demonstrates that the 5 mM K:D-rib solution slows the replication of the Hs 578T cell line and has a cytostatic effect on canine carcinoma cell line (A72) [ 11 ]. The effects of potassium ascorbate together with D-ribose have been investigated on Beckwith - Wiedemann syndrome and in a case of Prader Willi syndrome and Costello syndrome, severe syndromes characterized both by a high oncological risk and by high ROS concentration [ 12 ]–[ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our most recent work demonstrates that the 5 mM K: D-rib solution slows the replication of the Hs 578T cell line and has a cytostatic effect on canine carcinoma cell line (A72) [11]. The effects of potassium ascorbate together with D-ribose have been investigated on BeckwithWiedemann syndrome and in a case of Prader Willi syndrome and Costello syndrome, severe syndromes characterized both by a high oncological risk and by high ROS concentration [12][13][14].…”
Section: Introductionmentioning
confidence: 99%